Risk factors venous and arterial thrombosis in young women out of pregnancy - N. K. Vereina; T. V. Movchan; V. S. Chulkov («REMEDIUM GROUP» Ltd., 2020)
Introduction: to assess the influence of factors independently associated with arterial and venous thrombosis in women aged 18-44 years outside pregnancy.Material and methods. The case-control study included 319 women: the cases group included 134 patients with verified arterial and venous thrombosis, the control group included 185 patients without thrombosis. inclusion criteria: age 18-44 years; the presence of the first episode of instrumental^ verified arterial or venous thrombosis; consent to participate in the study. Exclusion criteria: pregnancy; the postpartum period up to 6 weeks at the time of thrombosis; mental disorders and mental illness. All women underwent clinical examination, collection of somatic and obstetric history, testing for biochemical parameters, hereditary and acquired thrombophilia. To quantify the independent relationships of risk factors with thrombotic events, the multiple logistic regression method was used.Results. In the group of cases, venous thrombosis was in 75% women, arterial thrombosis - in 25%. Ischemic strokes prevailed in the structure of arterial thrombosis. The most common trigger was the use of estrogen-progestin containing contraceptives in combination with other risk factors. In 23 cases (17.2%) the thrombosis were unprovoked. The proportion of women ≥ 40 years old, smoking intensity; family history of VTE in relatives up to 50 years of age, dyslipidemia, hyperfibrinogenemia, comorbidity, and the presence of thrombophilia met with a higher frequency in the group of cases. Independent factors associated with the development of arterial and venous thrombosis in young women were: the presence of diseases of the gallbladder (OR = 12,1 95% CI 2.5-67.5), cardiovascular diseases (OR = 10.2; 95% CI 3.6-29.1); total cholesterol level (OR = 7.7; 95% CI 4.4-13.5); respiratory diseases (OR = 3.7; 95% CI 1.0-11.5); the use of combined hormonal contraceptives (OR = 3.4; 95% CI 1.7-6.8); varicose veins of the lower extremities (OR = 2.5; 95% CI 1.0-4.9).Conclusion. The identification of the most important risk factors for arterial and venous thrombosis will expand the understanding of the common pathogenetic way of thrombosis in a population of women of childbearing age and improve their personalized prognosis and early prevention.